A Chlorotoxin‐Directed Diselenide‐Bridged Tumor‐Homing Persistent Luminescence Nanoprobes Mediating Inhibition of Oxidative Phosphorylation for Long‐Term Near‐Infrared Imaging and Therapy of Glioblastoma (Adv. Funct. Mater. 1/2023). (3rd January 2023) - Kong, Jianglong; Sun, Yuting; Ge, Xiaohan; Mao, Meiru; Yu, Hongrui; Wang, Yi
Abstract : Glioblastoma Targeted Therapy In article number 2209579, Wang and co‐workers report a near‐infrared persistent luminescence nanoparticle for the diagnosis and targeted therapy of glioblastoma (GBM). GBM cell membrane (GCM) coating and chlorotoxin enhanced the blood‐brain barrier (BBB) penetration and the targeting and tumor‐homing of GBM. This study offers an example of the highly promising drug carriers for precise diagnosis and therapy of central nervous system diseases.